Child Cohabitation in the Grip of Patriarchy: Between Cultural Normalization and Legal Void - Sri Nanang Meiske Kamba; Nur Mohamad Kasim; Waode Mustika (Universitas Negeri Gorontalo, 2025)
This study aims to examine the positive legal void in responding to the practice of child cohabitation in Indonesia and analyze the role of the patriarchal system in worsening the weak protection of children, especially girls. Using a juridical-normative method with a qualitative approach, this study examines national laws and regulations, international conventions, and critical legal literature to uncover structural inequalities in regulations. The results of the analysis show that child cohabitation is a form of covert sexual exploitation that has been allowed to take place in the social space without legal certainty due to legal-formalistic views and the dominance of patriarchal cultural norms. The state has failed to carry out its constitutional mandate in guaranteeing children's rights to protection, health, education, and self-development. Therefore, progressive legal reform, based on gender justice and based on the principles of the best interest of the child and maqasid al-shariah is needed as an urgent step to ensure comprehensive and transformative legal protection for Indonesian children.